Issues in economics today - Guell, Robert C. (Boston : McGraw-Hill Irwin, 2008)
This book is designed for a one semester issues-based general education economics course, and its purpose is to interest the nonbusiness, noneconomics major in what the discipline of economics can do.
Includes index.
aug 29/04/13
Loans
Keywords: Economics; International trade; Stock market